Морфометричні параметри видів роду Echinacea Moench при інтродукиіїу Донецький ботанічний сад НАН України - Журавель, Т.О. (Промышленная ботаника, 2004)
Problens of morphometric parameters variability of the following species of the genus Echinacea Moench under introduction to the south-east of Ukraine are considered: Echinacea purprea (L.) Moench, Echinacea angustifolia DC., Echinacea pallida (Nutt.) Nutt.